Electrophysiological effects of non-vitamin K antagonist oral anticoagulants on atrial repolarizing potassium channels - Wiedmann, Felix Tobias; Schlund, Daniel; Kraft, Manuel; Nietfeld, Jendrik; Katus, Hugo; Schmidt, Constanze; Thomas, Dierk (Europace, 2020)
Aims: Non-vitamin K antagonist oral anticoagulants (NOACs) are widely used in the prevention of stroke and systemic embolism in patients with non-valvular atrial fibrillation (AF). The efficacy of NOACs has been attributed in part to pleiotropic effects that are mediated through effects on thrombin, factor Xa, and their respective receptors. Direct pharmacological effects of NOACs and cardiac ion channels have not been addressed to date. We hypothesized that the favourable clinical outcome of NOAC use may be associated with previously unrecognized effects on atrial repolarizing potassium channels. Methods and results: This study was designed to elucidate acute pharmacological effects of NOACs on cloned ion channels Kv11.1, Kv1.5, Kv4.3, Kir2.1, Kir2.2, and K2P2.1 contributing to IKr, IKur, Ito, IK1, and IK2P K+ currents. Human genes, KCNH2, KCNA5, KCND3, KCNJ2, KCNJ12, and KCNK2, were heterologously expressed in Xenopus laevis oocytes, and currents were recorded using voltage-clamp electrophysiology. Apixaban, dabigatran, edoxaban, and rivaroxaban applied at 1 µM did not significantly affect peak current amplitudes of Kv11.1, Kv1.5, Kv4.3, Kir2.1, Kir2.2, or K2P2.1 K+ channels. Furthermore, biophysical characterization did not reveal significant effects of NOACs on current-voltage relationships of study channels. Conclusion: Apixaban, dabigatran, edoxaban, and rivaroxaban did not exhibit direct functional interactions with human atrial K+ channels underlying IKr, IKur, Ito, IK1, and IK2P currents that could account for beneficial clinical outcome associated with the drugs. Indirect or chronic effects and potential underlying signalling mechanisms remain to be investigated.